(untitled) (Journal of the College of Basic Education, 2022)
The current study aimed to identify the extent to which the middle school mathematics teachers possess the skills to solve the mathematical problem. In order to verify the goal, the following questions were formulated: 1) What is the difference between the real average and the hypothetical average for middle school mathematics teachers for math problem solving skills? 2) Do middle school mathematics teachers have the skills to solve the mathematical problem according to the variable (gender, years of service)? In order to achieve the goal of the research, the researcher adopted the descriptive research method, as the research sample consisted of (300) male and female teachers specializing in mathematics for the intermediate stage who were affiliated to the middle and secondary schools in the Directorate of Education in Diyala in the districts of Baquba and Muqdadiya and their sub-districts and villages, and the researcher prepared the research tool a questionnaire Mathematical problem solving skills, and the Mathematical problem solving skills questionnaire consisted of (4) main skills and (30) sub-indicators. The survey results showed the following: 1) The male and female teachers of the research sample have the ability to solve mathematical problems by 77% in the identification of mathematical problem solving skills prepared by the researcher. 2) Mathematics teachers possess the skills of solving the mathematical problem in the identification of the skills of solving the mathematical problem (according to the gender variable) and for the benefit of females. 3) The male and female teachers of the research sample who have served more than 10 years outperformed the male and female teachers of the research sample who have service less than 10 years in identifying mathematical problem solving skills according to NCTM standards. In light of the research results, a number of recommendations and suggestions were developed, the most important of which are: 1) Holding training courses for mathematics teachers and training them in mathematical thinking, as well as on mathematical problem solving skills. 2) Working on diversifying the methods, strategies and teaching methods presented to them in the mathematics curricula or that the teacher strives to practice during the lesson. 3) Motivating mathematics teachers to view scientific and local studies and research within their field of specialization and requesting them to prepare them. 4) Conducting a similar study for mathematics teachers and teachers in other stages. 5) Conducting a study to determine the extent to which students possess the skills of solving a mathematical problem. 6) Conducting empirical studies using modern teaching strategies to develop mathematical problem solving skills.